Fostering sustainability through technology-mediated interactions: Conviviality and reciprocity in the sharing economy. Issue 3 (18th February 2020) - Carrigan, Marylyn; Magrizos, Solon; Lazell, Jordon; Kostopoulos, Ioannis
Abstract : Purpose: This article addresses the lack of scholarly attention paid to the sharing economy from a sociological perspective, with respect to the technology-mediated interactions between sharing economy users. The paper provides a critical overview of the sharing economy and its impact on business and communities and explores how information technology can facilitate authentic, genuine sharing through exercising and enabling conviviality and non-direct reciprocity. Design/methodology/approach: The paper begins with a critique of the technology-mediated sharing economy, introduces the concept of conviviality as a tool to grow and shape community and sustainability within the sharing economy and then explores reciprocity and sharing behaviour. Finally, the paper draws upon social exchange theory to illustrate conviviality and reciprocity, using four case studies of technology-enabled sharing. Findings: The paper contributes to the emerging debate around how the sharing economy, driven by information systems and technology, affects social cohesion and personal relationships. The paper elucidates the central role conviviality and reciprocity play in explaining the paradoxes, tensions and impact of the sharing economy on society. Conviviality and reciprocity are positioned as key capabilities of a more sustainable version of the sharing economy, enabled via information technology. Originality/value: The findings reveal that information technology-mediated sharing enterprises should promote conviviality and reciprocity in order to deliver more positive environmental, economic and social benefits. The diversity of existing operations indicated by the findings and the controversies discussed will guide the critical study of the social potential of sharing economy to avoid treating all sharing alike.